Identification and characterization of a novel human adenovirus type HAdV-D116 - Zhou, Menglan; Chen, Wenjing; Zhang, Dong; Ma, Shicheng; Liu, Mange; Ren, Lili; Guo, Jiayu; Gao, Yi; Lu, Minya; Su, Huiting; Zhao, Ying; Xu, Yingchun; et al. (Frontiers in Microbiology, 2025)
IntroductionHuman adenovirus infections are typically associated with acute respiratory infection, keratoconjunctivitis, acute cystitis, hepatitis, and gastroenteritis, while central nervous system (CNS) related infections are rarely reported.MethodsIn this study, a novel human adenovirus was identified in the cerebrospinal fluid from an encephalitis patient with X-linked agammaglobulinemia via metagenomic next-generation sequencing (mNGS). Probe capture enrichment sequencing and PCR validation further confirmed the presence of this adenovirus in the patient’s cerebrospinal fluid.ResultsWhole-genome analysis classified the virus within the Human mastadenovirus D species, revealing an approximately 2000 bp deletion in the E3 gene that resulted in the loss of CR1-gamma and RID-alpha regions and the formation of a novel open reading frame (ORF). The penton base, hexon, and fiber genes were identified as P33H28F71, designating this virus as a novel type, subsequently named HAdV-D116 by the Human Adenovirus Working Group. Recombination analysis suggested that HAdV-D116 is a recombinant strain derived from HAdV-D33, HAdV-D28, and HAdV-D71. Structural analysis of the fiber-knob domain indicated that HAdV-D116 likely uses sialic acid as a receptor.DiscussionThe unique genomic features of HAdV-D116, combined with the patient’s immunodeficiency, are proposed to contribute to its possible CNS infectivity. The discovery of HAdV-D116 expands our understanding of human adenovirus tropism and underscores the need for vigilance regarding the emergence of novel adenovirus-related CNS infections.